The Influence of the Ion Implantation of Au– to the Microstructure of the Amorphous-nanocrystaline AlN-TiB2-TiSi2 - K.V. Smyrnova; А.A. Demianenko; A.S. Radko; A.V. Pshyk; O.V. Kuzovlev; H. Amekura; K. Oyoshi; Y. Takeda (Журнал нано- та електронної фізики)
Direct measurements were performed using TEM, HRTEM, XRD and SEM with microanalysis. The results showed that the thermal annealing at 1300 С in air leads to the formation of nanoscale phases 1015 nm from AlN, AlB2, Al2O3 and TiO2. Moreover, the ion implantation of the negative ions Au– causes fragmentation (decrease) of the size of nanograins to 2-5 nm with the formation of Au– clusters. In addition, the ion implantation leads to the formation of an amorphous oxide film in the depth (at the undersurface layer) of the coating.